A potential herbal therapeutic for trichinellosis - El-kady, Asmaa M.; Abdel-Rahman, Iman A. M.; Sayed, Eman; Wakid, Majed H.; Alobaid, Hussah M.; Mohamed, Khalil; Alshehri, Eman Abdullah; Elshazly, Hayam; Al-Megrin, Wafa Abdullah I.; Iqbal, Furhan; Elshabrawy, Hatem A.; Timsah, Ashraf G. (Frontiers in Veterinary Science, 2022)
Background: Trichinellosis is a helminthic disease caused by Trichinella spiralis via the ingestion of raw or undercooked meat of infected animals. Current estimates indicate that 11 million humans have trichinellosis, worldwide. The effective use of anti-trichinella medications is limited by side effects and resistance which highlight the critical need for safe and effective drugs, particularly those derived from medicinal plants. Therefore, in the present study, we aimed to evaluate the efficacy of the ethanolic extract of Artemisia annua (A. annua) in treatment of experimentally induced trichinellosis. Materials and Methods: Trichinellosis was induced experimentally in male 6-8 weeks BALB/c mice. BALB/c mice were divided into four groups, 10 mice each. One group was left uninfected and untreated, whereas three groups were infected with T. spiralis. One infected group of mice was left untreated (negative control) while the remaining two infected groups received either 300 mg/kg of the ethanolic extract of A. annua or 50 mg/kg of albendazole (positive control). All treatments started from the third day post-infection (dpi) for three successive days. All animals were sacrificed on the 7th dpi for evaluation of treatment efficacy. Results: Our findings showed that A. annua treatment reduced the T. spiralis adult-worm count in the intestine of infected animals. Moreover, treatment with A. annua restored the normal intestinal architecture, reduced edema, alleviated inflammation as demonstrated by reduced inflammatory infiltrate and expression of TGF-β in intestinal tissues of A. annua-treated animals compared to infected untreated animals. Conclusions: Our findings show that A. annua extract is effective in treating experimentally induced trichinellosis which highlight the therapeutic potential of A. annua for intestinal trichinellosis.